DISKURSUS ISLAM DALAM KONSTRUKSI MEDIA - Fahmi, Muhammad; Abdullah, Irwan; Noviani, Ratna; Udasmoro, Wening (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2015)
This paper aims to examine how the secular media in Surakarta represent Islam in the case of Charlie Hebdo. Therefore, this study used discourse analysis of Theo van Leeuwen focusing on how the subject or actor of the show in the media. This study concluded that the media represent Islam not only with “Western ideology” through idioms such as radical Islamist militants and terrorists, but also with